A novel aqueous ammonium dual-ion battery based on organic polymers. Issue 18 (17th April 2019) - Zhang, Yadi; An, Yufeng; Yin, Bo; Jiang, Jiangmin; Dong, Shengyang; Dou, Hui; Zhang, Xiaogang
Abstract : A novel and green aqueous ADIB with high cell voltage based on organic polymers. Abstract : Aqueous dual-ion batteries, one of the latest battery systems, have attracted considerable attention due to their merits of high safety, low cost and environment friendliness except for their high energy density and power density. However, the conventional employment of inorganic electrode materials usually leads to low power density and high cost. Herein, we present a novel aqueous ammonium dual-ion battery (ADIB) with a maximum operating voltage of 1.9 V, in which green and metal-free organic materials such as n-type polyimide and p-type radical polymers serve as anode and cathode, respectively, and 1 M ammonium sulfate solution acts as the electrolyte. During the charging process, the n-type polyimide can combine with cations, while p-type radical polymers can simultaneously accept anions, whereas the cations and anions can reversibly diffuse back to the electrolyte during the discharging process. This ingenious combination makes an assembled ADIB deliver a high energy density of 51.3 W h kg −1 and a maximum power density of 15.8 kW kg −1 (based on the total active weight of both cathode and anode), along with a good cycling stability with 86.4% capacity retention after 10 000 cycles at a current density of 5 A g −1 .